Regional distribution of the MTHFR C677T polymorphism in Chinese females - Lin, Hua; Liao, Changxi; Zhang, Rujing (Frontiers in Genetics, 2023)
Objective: For analyzing the distribution characteristics of MTHFR C677T genetic polymorphism in Chinese females to provide information for helping reduce birth defects and formulate public health policies to prevent congenital malformations. Methods: Literature search in the last 6 years on "MTHFR C677T", "polymorphism" and "methylene tetrahydrofolate reductase". The included literature provides the MTHFR C677T frequency in the robust females in the corresponding regions. The data were grouped by the national administrative region as a unit to obtain the distribution information of the MTHFR C677T as well as alleles in the female population in every province, municipality or autonomous regions. For analyzing the overall distribution of MTHFR C677T allele and the geographical distribution of pregnancy complications. Results: A total of 126 studies were included, covering five autonomous areas, four municipalities directly under the Central Government, as well as 22 provinces (except Taiwan Province) in China. MTHFR C677T polymorphism data of 27 groups of Chinese Han women and 31 groups of other Chinese females were obtained, and the chi-square test revealed notable inter-group differences (p=0.000). The TT genotype and T allele of MTHFR C677T accounted for 18.2% (4.7%-38.3%) and 40.3% (19.7%-61.4%) of the Chinese female population, respectively, with a large north-south difference. Chinese females had a consistent frequency of T allele with the geographical distribution of pregnancy complications such as recurrent abortion and preeclampsia. Conclusion: With an obvious geographical gradient, the MTHFR C677T polymorphism distribution in Chinese females is consistent with the geographical distribution of multiple pregnancy complications, and the risk assessment of it might be included in primary prevention for birth defects.